Pengaruh kurs, net ekspor, dan penanaman modal asing terhadap pertumbuhan ekonomi Indonesia - Tuty Cahya Azizah; Haryadi Haryadi; Etik Umiyati (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
The purpose of this study is to analyze the development of exchange rates, net exports, FDI, and Indonesia's economic growth in 1998-2017 and to analyze the effect of exchange rates, net exports, and foreign investment (FDI) on Indonesia's economic growth in 1998-2017. used in this study is secondary data sourced from the Central Statistics Agency (BPS). The analytical tool used in this study is descriptive and quantitative analysis, namely by multiple linear regression. The research method used in this study is the